2015
DOI: 10.1080/13607863.2015.1035696
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated increase and decrease in subjective age as a function of changes in loneliness and objective social indicators over a four-year period: results from the health and retirement study

Abstract: This is one of very few studies that examined changes in subjective age over time. Changes in subjective age represent an important construct that corresponding to other changes in subjective experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 51 publications
2
25
0
Order By: Relevance
“…Moreover, the percentage of those who demonstrated a relative decrease in subjective age was similar to those who demonstrated an accelerated increase. This distribution not only supports previous findings showing a gap in the second half of life between the objective and the subjective perception of age (i.e., Rubin and Berntsen 2006), but also reflects the non-linear perception of time along the passage of years (Ayalon et al 2015).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, the percentage of those who demonstrated a relative decrease in subjective age was similar to those who demonstrated an accelerated increase. This distribution not only supports previous findings showing a gap in the second half of life between the objective and the subjective perception of age (i.e., Rubin and Berntsen 2006), but also reflects the non-linear perception of time along the passage of years (Ayalon et al 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Hence, we examined an accelerated increase vs. a relative decrease in subjective age. In line with a previous examination of changes in age perceptions (Ayalon et al 2015), an accelerated increase in subjective age over the 4-year period of the study was defined as an increase in subjective age that was greater than 5 years. A relative decrease in subjective age was defined as a difference in subjective age between 2012 and 2008 that was lower than 3 years.…”
Section: The Present Studymentioning
confidence: 87%
“…The cravings may be stronger, more intrusive and involve more vivid imagery among people who suffer from a large cluster of ADHD symptoms, because these symptoms reduce people's ability to divert their attention from intrusive thoughts (Malloy-Diniz et al, 2007 ) and the use of SNS can be very rewarding for such individuals; children and adolescents with ADHD symptoms present hyper-responsiveness to social rewards (Kohls et al, 2009 ) which are often provided by SNS. This presumably happens because the use of the SNS can help such individuals present themselves in a more positive light (Gil-Or et al, 2015 ), escape their daily sorrows (Masur et al, 2014 ), increase their self-esteem and sociability (Zywica and Danowski, 2008 ), and reduce their loneliness (Deters and Mehl, 2013 ). Since the presence of ADHD symptoms often induces stress (Randazzo et al, 2008 ; Hirvikoski et al, 2009 ) and reduces people's self-esteem (Bussing et al, 2000 ; Richman et al, 2010 ), it is reasonable to assume that the magnitude of cravings to use the SNS is at least in part influenced by such aversive psychological states which result, at least in part, from having ADHD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between social activities and subjective age is not well characterised even though the relationship of physical and psychological factors with subjective age has been widely reported. The only study that prospectively investigated the covariates of subjective age showed that a decrease in loneliness was associated with a younger subjective age, whereas an increase in depressive symptoms was associated with older subjective age [15]. With respect to the relationship between subjective age and social activity in the elderly, including participation in community activities and social roles that rank higher than instrumental activities of daily living (IADLs), one study evaluated the number of social contacts such as conversations and telephone calls.…”
Section: Introductionmentioning
confidence: 99%